Progress in pattern recognition, image analysis and applications 11th Iberoamerican Congress on Pattern Recognition, CIARP 2006, Cancún, Mexico, November 14-17, 2006, proceedings - Iberoamerican Congress on Pattern Recognition (Lecture notes in computer science ;, 2006)
This book constitutes the refereed proceedings of the 11th Iberoamerican Congress on Pattern Recognition, CIARP 2006, held in Cancun, Mexico in November 2006. The 99 revised full papers presented together with 3 keynote articles were carefully reviewed and selected from 239 submissions. The papers cover ongoing research and mathematical methods for pattern recognition, image analysis, and applications in such diverse areas as computer vision, robotics and remote sensing, industry, health, space exploration, data mining, document analysis, natural language processing and speech recognition.